A CHARMING GERMAN IN THE JAWS OF AMERICAN POLITICS: US Influence on Willy Brandt’s Political Profiling and Eastern Politics - Beštić-Bronza, Slavojka (Politeia, 2020)
The aim of this paper is to show to what extent and by what mechanisms the United States influenced the political formation of the personality and activities of West German Chancellor Willy Brandt. Special emphasis was placed on American influences during the implementation of Brandt’s most famous political concept, "Eastern Politics", which places the chronological context of the development of relations in line with pan-European and world political movements, and their correlation with Brandt’s political path in exile and later in occupied Germany, and finally in the newly created independent Federal Republic of Germany. Circumstances, personal (dis)inclinations and mutual influences gave birth to a rather ambivalent relationship, created mainly due to the interests of both parties, which overlapped in certain periods of time, while later they moved away and became cold, even often hostile.